An Interview with U.N. Secretary-General Kofi A. Annan - Annan, Kofi (Tufts Archival Research Center, 2005)
Volume 21, Issue 2. Summer/Fall The secretary-general describes the evolving concept of sovereignty and the importance of the United Nations in maintaining global security.